Tästäkin selvitään yhdessä – retoriikka merkityksellistämisen välineenä pandemian johtamisessa - Einola, Suvi; Kohtamäki, Marko; Kinnunen, Marina; Berg, Päivi (Hallinnon tutkimuksen seura, 2023)
We will get through this together– rhetoric as a sensemaking practice in managing a pandemic In a poorly managed crisis situations, inconsistent management produces cacophony, ambiguity and anxiety that disrupts optimal thinking and action. At best, consistently used rhetorics can help the handling and management of the pandemic. This study approaches pandemic management from a rhetorical perspective, looking at the role of rhetoric as part of the sensemaking process. We use a single case data to understand the rhetoric used in the case of Wellbeing Services County of Ostrobothnia. We identify three primary rhetoric: persuasion, encouragement, and obligation. We describe how these rhetoric were used to manage the sensemaking processes within the region.
Keywords: rhetoric; sensemaking; pandemic management; fi=Henkilöstöjohtaminen|en=Human Resource Management|; fi=Strateginen johtaminen|en=Strategic Management|